2014
DOI: 10.1016/j.tins.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Illicit dopamine transients: Reconciling actions of abused drugs

Abstract: Phasic increases in brain dopamine are required for cue-directed reward seeking. While compelling within the framework of appetitive behavior, the view that illicit drugs hijack reward circuits by hyper-activating these dopamine transients is inconsistent with established psychostimulant pharmacology. However, recent work reclassifying amphetamine (AMPH), cocaine, and other addictive dopamine-transporter inhibitors (DAT-Is) supports transient hyper-activation as a unifying hypothesis of abused drugs. We argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 128 publications
(221 reference statements)
8
92
0
1
Order By: Relevance
“…Dopamine transients are increased following administration of drugs of abuse (12), and this appears to mediate their reinforcing properties (14). Dopamine transients have been studied extensively (1-13, 31-35); however, previous measurements were restricted to a single hemisphere, including those using a magnetic resonance imaging-compatible dopamine reporter (42), and few microdialysis experiments performed bilateral measurements (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dopamine transients are increased following administration of drugs of abuse (12), and this appears to mediate their reinforcing properties (14). Dopamine transients have been studied extensively (1-13, 31-35); however, previous measurements were restricted to a single hemisphere, including those using a magnetic resonance imaging-compatible dopamine reporter (42), and few microdialysis experiments performed bilateral measurements (43).…”
Section: Discussionmentioning
confidence: 99%
“…Given that amphetamine-induced dopamine transients remained in the unilaterally lesioned animals, it is apparent that interhemispherical connectivity contributes to psychostimulant-induced dopamine fluctuations. Dopamine transients, which have been shown to be important in drug abuse (14), clearly arise from bilateral interactions. Furthermore, amphetamines are used to treat attention deficit hyperactivity disorder (ADHD), and patients with ADHD have abnormal frontostriatal asymmetry (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of decreased dopamine output and recruitment of noradrenergic signaling revealed in this work suggests the negative reinforcement model of drug use may develop after the first drug exposure and withdrawal episode. Drugs of abuse increase dopamine overflow in the NAc (Covey et al, 2014), which helps drive their acutely reinforcing properties, and a recent study showed intravenous morphine administration produces similar efflux (Vander Weele et al, 2014). We gave morphine s.c. since i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs of abuse have diverse actions on dopaminergic signaling in the ventral tegmental area (VTA) and its afferents (Juarez and Han, 2016), where dopamine is thought to aid in associative memory formation and drive cue-induced drug seeking (Berke and Hyman, 2000;Everitt and Robbins, 2005;Hyman et al, 2006). Action potentials from the VTA drive transient dopamine concentration fluctuations in the nucleus accumbens (NAc) (Sombers et al, 2009) that increase following drug administration and can potentiate a drug's positively reinforcing properties (Covey et al, 2014). However, NAc dopamine may also play a role in the negatively reinforced component of drug abuse, since dopamine overflow is suppressed during noxious and aversive stimuli (Park et al, 2015;Roitman et al, 2008;Twining et al, 2015).…”
Section: Introductionmentioning
confidence: 99%